Problem Based Learning Effect Using the TaRL Approach on Problem-Solving Skills in Global Warming Topic - Eisha Jansyah Yusuf; Devi Solehat; Fuji Hernawati Kusumah (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
Physics learning is often considered difficult because students are unable to relate concepts to real-world problems they encounter. This condition results in low problem-solving skills among students, especially on contextual topics such as global warming. This study aims to determine the effect of the Problem Based Learning (PBL) model with the Teaching at the Right Level (TaRL) approach on students' problem-solving skills in global warming material. The research method used was quantitative with a quasi-experimental design of the pretest- posttest control group type. The research subjects consisted of 64 tenth-grade students at SMA Negeri 87 Jakarta, divided into an experimental class using the PBL-TaRL model and a control class using scientific learning. The research instrument was an essay test of problem-solving skills based on Polya's stages. The results showed that the average posttest score of the experimental class was higher than that of the control class. Based on the Ngain results, the N- gain was 0.58 (medium category) for the experimental group compared to 0.29 (low category) for the control group. Thus, the Problem Based Learning (PBL) model with the Teaching at the Right Level (TaRL) approach had a significant effect on students' problem-solving skills in global warming material.